Neutron Methods for Archaeology and Cultural Heritage - Kardjilov, Nikolay; Festa, Giulia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an extensive overview of the application of neutron characterization techniques in cultural heritage to a broad audience and will be of interest to both scientists and non-scientists in the field. Archaeologists, paleontologists, restaurateurs and conservators, historians and collectors will be fascinated by the wealth of information that can be obtained using neutron techniques, while material scientists and engineers will find details of the experimental techniques and materials properties that can be determined. Neutrons, due to their weak interactions with materials, provide a penetrating, but non-invasive probe of bulk properties. They allow the characterization of the composition and mechanical properties of materials, helping to answer questions related to the dating, the manufacturing process or the state of degradation of artefacts. They allow detailed interrogation of the internal structures of objects that may be otherwise hidden from view. The first section of the book is dedicated to stories describing spectacular discoveries brought about by the use of neutron techniques in a range of applications. The second section covers the experimental techniques in appropriate detail: basic principles, limitations and fields of application. .
Part I Cultural Heritage and Neutrons -- 1. Probing our Heritage with Neutrons - One Successful Story -- 2. Bronze Sculptures and Lead Objects tell Stories about their Creators -- 3. Paintings Reveal their Secrets -- 4. Neutrons Unveil Secrets of Musical Instruments -- 5. The Glory of Ancient Weapons and Armors; F. Salvemini -- 6. Ceramics, Marbles and Stones in the Light of Neutrons -- 7. Paleontology - Fossilized Ancestors Re-Awaken by Neutron Radiography -- Part II Experimental Methods -- 8. General Introduction to Neutron Physics and Instrumentation -- 9. Scattering Techniques: Small- and Wide-Angle Neutron Diffraction -- 10. Nuclear Analysis Techniques -- 11. Nuclear Analysis Imaging Techniques -- 12. Neutron Activation Autoradiography -- 13. Neutron imaging.
Keywords: Materials -- Analysis; Particle accelerators; Cultural property; Archaeology; Surfaces (Technology).; Thin films; Characterization and Analytical Technique; Accelerator Physics; Cultural Heritage; Archaeology; Surfaces, Interfaces and Thin Film